2017
DOI: 10.1136/heartjnl-2016-310677
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific outcomes with addition of defibrillation to resynchronisation therapy in patients with heart failure

Abstract: In primary prevention patients with CRT indication, the addition of a defibrillator might convey additional benefit only in well-selected male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
(35 reference statements)
2
17
1
Order By: Relevance
“…A metaanalysis of 5 major randomized clinical trials of ICD therapy found a mortality benefit in men (HR: 0.78, 95% CI: 0.70-0.87, P < 0.001) but not in women (HR: 1.01, 95% CI: 0.76-1.33, P = 0.95). 31 Barra et al 32 women. This study concluded that the addition of a defibrillator to CRT might convey a benefit only in well-selected male patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A metaanalysis of 5 major randomized clinical trials of ICD therapy found a mortality benefit in men (HR: 0.78, 95% CI: 0.70-0.87, P < 0.001) but not in women (HR: 1.01, 95% CI: 0.76-1.33, P = 0.95). 31 Barra et al 32 women. This study concluded that the addition of a defibrillator to CRT might convey a benefit only in well-selected male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Barra et al performed an observational multicenter cohort study in 5307 patients with ischemic or nonischemic dilated cardiomyopathy with no history of sustained ventricular arrhythmias. They compared survival in patients with CRT‐D with patients with CRT without defibrillator functionality (CRT–pacemaker [CRT‐P]) and stratified the results by sex.…”
Section: Implantable Cardioverter‐defibrillatorsmentioning
confidence: 99%
“…More and more, patients want to know what to expect from a treatment option, and are more frequently requesting to be empowered in decisions regarding their management [28]. In patients meeting guideline criteria, when chances of response are low discussion may involve the choice between a CRT-D or a CRT-P device [29], or considering novel approaches like LV endocardial pacing [10], or multipoint pacing [8] at an early stage if non-responder status if confirmed. Use of auto-optimization algorithms [9], and optimization of medical therapy with novel drugs [11,12] should be pursued in this group of patients to optimize chances of response and survival in this group.…”
Section: Liu Et Al Have Shown That For Same Levels Of Lvef Patientsmentioning
confidence: 99%
“…Responders, especially superresponders to CRT, are at relatively lower risk of long-term cardiac mortality (3). Whether the primary prevention implantable cardioverter-defibrillator (ICD) improves outcomes over and above CRT is a matter of ongoing debate (4)(5)(6)(7), with the recent CeRtiTuDe cohort study revealing that the majority of the excess mortality among CRT-Pacemaker (CRT-P) subjects at 2-year follow-up is related to an increase in non-SCD (8).…”
Section: Introductionmentioning
confidence: 99%